The factor that influence the daily diet among wellness student in universiti malaysia kelantan, kampus kota - Fazlin Anita Ahmad; Nur Fatin Azranuddin; Nur Shayhira Shamsuddin; Nur Umirah Saffian (2022)
Daily diet is a way to reduce the obesity problem that is happening now. Those who practise a daily diet should take their food according to the correct portion. A balanced diet can be referred to through the food pyramid. For example, bread, meat, milk and so on. This study took about 2 months, from November 2022 until January 2023. This study was conducted to identify factors that influence daily diet among Wellness students at the Universiti Malaysia Kelantan, Kampus Kota. A pilot study conducted on Wellness students totalling 124 people as a respondent at Universiti Malaysia Kelantan, Kampus Kota. This data was collected through the distribution of survey forms which showed a good response rate. The results of this study were done to give awareness to students, especially Wellness students, about the factors that affect their daily nutrition. The results of this study can also be used as a reference to health centres or nutritionists. Keywords: Daily Diet, Individual Factors, Social Factors, Environment Factors